Inhibition of Fatty Acid Oxidation as a New Target To Treat Primary Amoebic Meningoencephalitis - Sarink, Maarten J; Tielens, Aloysius G M; Verbon, Annelies; Sutak, Robert; van Hellemond, Jaap J (Antimicrobial agents and chemotherapy, 2020)
Primary amoebic meningoencephalitis (PAM) is a rapidly fatal infection caused by the free-living amoeba Naegleria fowleri The amoeba migrates along the olfactory nerve to the brain, resulting in seizures, coma, and, eventually, death. Previous research has shown that Naegleria gruberi, a close relative of N. fowleri, prefers lipids over glucose as an energy source. Therefore, we tested several already-approved inhibitors of fatty acid oxidation alongside the currently used drugs amphotericin B and miltefosine. Our data demonstrate that etomoxir, orlistat, perhexiline, thioridazine, and valproic acid inhibited growth of N. gruberi We then tested these compounds on N. fowleri and found etomoxir, perhexiline, and thioridazine to be effective growth inhibitors. Hence, not only are lipids the preferred food source for N. gruberi, but also oxidation of fatty acids seems to be essential for growth of N. fowleri Inhibition of fatty acid oxidation could result in new treatment options, as thioridazine inhibits N. fowleri growth in concentrations that can be reached at the site of infection. It could also potentiate currently used therapy, as checkerboard assays revealed synergy between miltefosine and etomoxir. Animal testing should be performed to confirm the added value of these inhibitors. Although the development of new drugs and randomized controlled trials for this rare disease are nearly impossible, inhibition of fatty acid oxidation seems a promising strategy as we showed effectivity of several drugs that are or have been in use and that thus could be repurposed to treat PAM in the future.
Keywords: Meningoencephalitis; therapy; drug targets; Naegleria gruberi; mastné kyseliny; Central Nervous System Protozoal Infections; protozoární infekce centrálního nervového systému; thioridazine; Fatty Acids; energy metabolism; Naegleria; treatment; Animals; amfotericin B; Naegleria fowleri; Amphotericin B; zvířata; meningoencefalitida; lipid metabolism